Association of infertility with premature mortality among US women: Prospective cohort study - Yi-Xin Wang; Leslie V. Farland; Siwen Wang; Audrey J. Gaskins; Liang Wang; Janet W. Rich-Edwards; Rulla Tamimi; Stacey A. Missmer; Jorge E. Chavarro (Elsevier, 2022)
Summary: Background: Infertility has been associated with common chronic non-communicable diseases. However, the association of infertility with long-term mortality is unclear. Methods: We followed 101,777 women aged 25-42 years at enrollment between 1989 and 2017. Biennial questionnaires updated participants' infertility status and underlying reasons for infertility throughout their reproductive lifespan. Hazard ratios (HRs) for the associations of infertility with the risk of premature mortality (death before age 70 years) were estimated using Cox proportional hazards models. Findings: During 28 years of follow-up, 2174 women died before age 70 years. Infertility was associated with an HR of 1.26 (95% confidence interval: 1.15 to 1.38) for premature death. This relation was largely driven by deaths from cancer (HR = 1.22, 1.08 to 1.39) and was stronger among women reporting infertility at a younger age (HR = 1.35, 1.19 to 1.52 for age ≤ 25 years; 1.23, 1.10 to 1.38 for age 26-30 years; and 1.10, 0.91 to 1.32 for age > 30 years, compared to no infertility). The premature mortality risk was also higher for women who didn't become pregnant after their first report of infertility (HR = 1.39, 1.25 to 1.54) than among women who reported at least one pregnancy after infertility (HR = 1.12, 1.00 to 1.26). When contributing diagnoses of infertility were evaluated, a greater risk of all-cause mortality was associated with infertility due to ovulatory disorders (HR = 1.28, 1.09 to 1.51) and endometriosis (HR = 1.50, 1.22 to 1.83). Interpretation: Infertility may be associated with a greater risk of premature mortality, particularly cancer mortality. Funding: The National Institutes of Health grants.